2020
DOI: 10.4103/ijpvm.ijpvm_290_19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aquatic exercise on dimensions of quality of life and blood indicators in patients with beta-thalassemia major

Abstract: Background: Thalassemia is considered as a group of genetic blood disorders, characterized by anemia. The present research aimed at evaluating the effects of aquatic exercise on quality of life and blood indices in patients with beta-thalassemia major. Methods: A clinical trial study involving 40 patients with thalassemia major, divided into two groups: experimental and control. The tools used to collect the data included demographic information questionnaire, blood ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition to clinical conditions, it appears that alterations in lifestyle, social relationships, and psychological events showed improvement in treatment outcomes ( 93 , 94 ). Furthermore, it was observed that regular exercise programs combined with drug therapy and blood transfusion can improve HRQOL in beta-thalassemia patients ( 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to clinical conditions, it appears that alterations in lifestyle, social relationships, and psychological events showed improvement in treatment outcomes ( 93 , 94 ). Furthermore, it was observed that regular exercise programs combined with drug therapy and blood transfusion can improve HRQOL in beta-thalassemia patients ( 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wagner et al [ 29 ], measuring CPET and vigorous-intensity physical activity using a triaxial accelerometer in 502 subjects from the general population, found a strong positive association with higher V’O 2 peak and other performance-related CPET parameters, supporting the implementation of higher-intensity aerobic exercise in health promotion. Exercise, especially aerobic activities, demonstrated to improve the QoL in TM patients [ 30 ]. Unfortunately, few TM patients perform a regular physical activity due to misconception that anaemia is a limiting factor, and virtually no one is recruited in a program of physical rehabilitation that may help to reduce exercise intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, few TM patients perform a regular physical activity due to misconception that anaemia is a limiting factor, and virtually no one is recruited in a program of physical rehabilitation that may help to reduce exercise intolerance. No proper exercise program has been designed yet for these patients, but a planned walking program is recommended to improve their QoL, and a regular aquatic exercise program helps patients to maintain or increase the level of performance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators observed an improvement in self-reported quality of life measures in the experimental cohort, which was attributed to exercise. More recently, 40 adult TDT patients were assigned to water exercise three times per week for 8 weeks [ 37 ]. Similar positive effects on quality of life were observed following this exercise regimen, reinforcing the potential beneficial effect of exercise in Thal.…”
Section: Discussionmentioning
confidence: 99%